Renal Cortical Pallor—A Useful Macroscopic Marker for Metabolic Derangements at Autopsy. Issue 3 (12th March 2013) - Zhou, Chong; Yool, Andrea; Byard, Roger W.
Abstract: Renal cortical pallor was studied as a potential marker at autopsy of diabetic ketoacidosis in 23 cases, hyperglycemic nonketotic coma in eight cases, and alcoholic ketoacidosis in five cases (vitreous humor glucose level ≥11.1 mM; β‐hydroxybutyrate level ≥5 mM). Renal cortical pallor was noted on macroscopic examination in 10 of 23 cases of lethal diabetic ketoacidosis (43.5%), three of eight cases of fatal hyperglycemic nonketotic coma (37.5%), and in two of five cases of alcoholic ketoacidosis (40%). Histologic examination revealed basal vacuolization of renal tubular epithelial cells in 12 cases, Armanni–Ebstein lesions in 10, and osmotic nephrosis in three. Although renal cortical pallor did not appear to be a particularly sensitive marker for hyperglycemia or ketoacidosis, and did not correlate with the severity of these parameters, it may still represent a useful macroscopic marker for underlying metabolic conditions at autopsy and should therefore prompt measurement of vitreous humor glucose and β‐hydroxybutyrate levels.